Attention control in mood and anxiety disorders: evidence from the antisaccade task. (8th May 2013) - Ainsworth, Ben; Garner, Matthew
<x xml:space="preserve">Abstract</x> The antisaccade task (in which participants must suppress a reflexive saccade towards a sudden, peripheral stimulus and generate a volitional saccade in the opposite direction) is considered a measure of cognitive inhibition. The task has been used to examine cognitive control deficits in several neuropsychiatric conditions, most notably schizophrenia. This commentary summarizes recent evidence from antisaccade tasks in mood and anxiety disorders, with reference to neuropsychological models and psychopharmacological mechanisms. Copyright © 2013 John Wiley & Sons, Ltd.